The Effect of Remuneration, Time Management, on Employee Performance through Organizational Citizenship Behaviour as Intervening - Pratama, Raditya Yuniar Alfani; Mujanah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2024)
The purpose of this study was to analyze the effect of remuneration, time management, on employee performance with organizational citizenship behavior as an intervening variable at Archives and Library Service Surabaya City. The sampling technique used is total sampling (saturated sample). The research sample was 40 respondents. Data collection using a questionnaire distributed to all respondents. The data collected was then analyzed using SEM-PLS analysis techniques. Results showed that remuneration has a positive and significant effect on organizational citizenship behavior. Remuneration has a positive and significant effect on organizational citizenship behavior. Remuneration has a negative and significant effect on employee performance. Time management has a positive and significant effect on organizational citizenship behavior. Time management has a positive and significant effect on employee performance. organizational citizenship behavior is negative and significant to employee performance. The effect of Remuneration has a negative and significant effect on Employee Performance with Organizational Citizenship Behavior as Mediation. The effect of Time Management has a negative and significant effect on Employee Performance with Organizational Citizenship Behavior as Mediation.